2022
DOI: 10.1186/s12944-021-01615-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism within the bone micro-environment is closely associated with bone metabolism in physiological and pathophysiological stages

Abstract: Recent advances in society have resulted in the emergence of both hyperlipidemia and obesity as life-threatening conditions in people with implications for various types of diseases, such as cardiovascular diseases and cancer. This is further complicated by a global rise in the aging population, especially menopausal women, who mostly suffer from overweight and bone loss simultaneously. Interestingly, clinical observations in these women suggest that osteoarthritis may be linked to a higher body mass index (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 103 publications
1
23
0
Order By: Relevance
“…Their introduction to the pharmacological sphere has considerably reduced the incidence of pathological fractures and consequent rates of disability in patients with osteoporosis. Novel evidence suggests that there may be a role for their use in reducing the progression of CAD via their effects on atheroma formation 8 9. Bisphosphonates have been shown to inhibit the progression of ectopic calcification through inhibitory action on the crucial regulatory enzyme, farnesyl pyrophosphate synthase, in the mevalonic acid pathway, which is implicated in both bone and lipid metabolism 8 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their introduction to the pharmacological sphere has considerably reduced the incidence of pathological fractures and consequent rates of disability in patients with osteoporosis. Novel evidence suggests that there may be a role for their use in reducing the progression of CAD via their effects on atheroma formation 8 9. Bisphosphonates have been shown to inhibit the progression of ectopic calcification through inhibitory action on the crucial regulatory enzyme, farnesyl pyrophosphate synthase, in the mevalonic acid pathway, which is implicated in both bone and lipid metabolism 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Novel evidence suggests that there may be a role for their use in reducing the progression of CAD via their effects on atheroma formation 8 9. Bisphosphonates have been shown to inhibit the progression of ectopic calcification through inhibitory action on the crucial regulatory enzyme, farnesyl pyrophosphate synthase, in the mevalonic acid pathway, which is implicated in both bone and lipid metabolism 8 9. RANKL inhibitors interfere with the glycoprotein, osteoprotegerin (OPG) and other signalling pathways, again involved in lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…(28)(29)(30) Therefore, high cholesterol, in particular high LDL, can cause imbalance in the regulation of bone formation and resorption, resulting in bone quality decrease. (31,32) While no previous data exist on the relationship between serum lipid levels and marrow adiposity in humans with T2D, Slade et al reported a positive association between serum cholesterol level and marrow adiposity in humans with T1D. (22) This correlation has also been documented in people without diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies in the literature have examined the molecular mechanisms correlated with cholesterol-mediated bone deterioration (reviewed in [ 15 ]). High total cholesterol levels are negatively associated with BMD, while treatment with cholesterol-lowering drugs (statins) promotes bone production and thus enhances BMD [ 22 , 23 ]. Clinical studies investigating the changes in lipid metabolism and the levels of lipid molecules associated with LBMD in humans are limited.…”
Section: Discussionmentioning
confidence: 99%